The adaptive compensations in endocrine pancreas from glucocorticoid-treated rats are reversible after the interruption of treatment - Rafacho, A. [UNESP]; Quallio, S.; Ribeiro, D. L. [UNESP]; Taboga, S. R. [UNESP]; Paula, F. M. M.; Boschero, A. C.; Bosqueiro, José Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Aim:Glucocorticoid administration induces insulin resistance (IR) and enhances islet mass and insulin secretion in rodents and humans. Here, we analysed whether these effects are still present after the interruption of dexamethasone treatment.Methods:Adult Wistar rats were distributed into CTL (daily injection of saline for five consecutive days), DEX (daily injection of 1 mg kg-1 body wt of dexamethasone for five consecutive days) and DEX(10) (5 days of dexamethasone treatment, followed by a period of 10 days without dexamethasone).Results:In vivo experiments indicated that the marked hyperinsulinemia found in DEX rats during fasting and fed states was normalized in the DEX(10) group. Furthermore, the IR and glucose intolerance observed in DEX were restored in DEX(10) rats. Islets from DEX rats secreted more insulin in response to increasing concentrations of glucose and other metabolic and non-metabolic stimuli, compared with that in the CTL group. The insulin secretion for the most compounds studied returned to CTL values in DEX(10) islets. Increased insulin secretion correlated well with the augmentation in beta-cell proliferation and mass in DEX rats, and these morphological alterations were normalized in islets from DEX(10) rats. In parallel, the increased levels of proteins involved in beta-cell proliferation such as Cd2 and Cdk4 observed in DEX islets were also normalized in DEX(10) islets.Conclusion:These data strongly support the view that almost all the morphophysiological alterations induced by dexamethasone in the endocrine pancreas are reverted after discontinuation of the treatment. This information is important, considering the frequent use of glucocorticoids in humans.
Keywords: beta-cell mass; dexamethasone; endocrine pancreas; glucocorticoid; insulin and glucose sensitivity; insulin secretion